The Effectiveness of Criminal Sanctions in Combating Corruption Crimes in Indonesia - Nayla Nayla (PT. Anagata Sembagi Education, 2024)
Combating corruption is a major challenge within Indonesia's criminal justice system. One of the key instruments in this effort is the imposition of firm and effective criminal sanctions. This study aims to examine the effectiveness of criminal sanctions against perpetrators of corruption and their impact on anti-corruption efforts in Indonesia. The research method used is a normative juridical approach, utilizing secondary data from legislation, court rulings, and related literature. The results show that although Indonesia has a strong legal foundation, such as Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 on the Eradication of Corruption Crimes, its implementation still faces various obstacles, such as sentencing disparities, lack of deterrent effect, and weak law enforcement. This study concludes that reform is needed in the criminal justice system for corruption, including enhancing the capacity of law enforcement, and harmonizing criminal sanctions to maximize deterrence. This study is expected to contribute to strengthening criminal law in addressing corruption as an extraordinary crime.